1993
DOI: 10.1093/nar/21.2.295
|View full text |Cite
|
Sign up to set email alerts
|

The cysteine conserved among DNA cytosine methylasesis required for methyl transfer, but not for specific DNA binding

Abstract: All DNA (cytosine-5)-methyltransferases contain a single conserved cysteine. It has been proposed that this cysteine initiates catalysis by attacking the C6 of cytosine and thereby activating the normally inert C5 position. We show here that substitutions of this cysteine in the E. coli methylase M. EcoRII with either serine or tryptophan results in a complete loss of ability to transfer methyl groups to DNA. Interestingly, mutants with either serine or glycine substitution bind tightly to substrate DNA. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 26 publications
6
65
0
Order By: Relevance
“…and G.L.V., unpublished results). Similar observations have been reported with the bacterial homologues of the human MTase [22,23]. Baits I-IV were first tested for their ability to activate the transcription of lacZ and LEU2 reporter constructs, each driven by multiple LexA operators.…”
Section: Two Regions Of Human Mtase Can Be Used As Baitssupporting
confidence: 56%
“…and G.L.V., unpublished results). Similar observations have been reported with the bacterial homologues of the human MTase [22,23]. Baits I-IV were first tested for their ability to activate the transcription of lacZ and LEU2 reporter constructs, each driven by multiple LexA operators.…”
Section: Two Regions Of Human Mtase Can Be Used As Baitssupporting
confidence: 56%
“…17,24 Covalent complex formation has been confirmed to be dependent on the cysteine residue in the PCQ motif. [25][26][27] In addition, the importance of the conserved cysteine and glutamic acid residues for catalysis has been shown by site directed mutagenesis in some cases. [25][26][27][28][29] …”
Section: Chemistry Of Dna Methylationmentioning
confidence: 99%
“…14,[25][26][27]56,57 The mechanism of the inhibition of DNA MTases by 5-aza-C and 5-FCdR has been demonstrated by chemical, mutational and structural analyses mostly with the prokaryotic cytosine MTases. The formation of a covalent complex between the catalytic cysteine residue and 5-aza-dC or 5-F-dC incorporated DNA has been biochemically demonstrated in several experimental systems 14,[25][26][27][50][51][52][53][54]56,57 and observed in structures of complexes between DNA-(cytosine-C5)-MTases and DNA (Fig. 5).…”
Section: Mechanism Of Inhibition Of the Drugs Targeting Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…formed to determine the role of this Cys showed that its substitution by other amino acids resulted in a complete loss of function by the MTases, M.EcoRII, M.HhaI, M.HaelII, M.Dcm [10][11][12][13]. Furthermore, introduction of 5-fluorocytosine in the DNA target resulted in the formation of trapped intermediates [13][14][15].…”
Section: Introductionmentioning
confidence: 99%